Professional self-determination as a condition for the development of personality subjectivity - Gaponova, S.A.; Serebryakova, T.A.; Minaeva, E.V. (Bulletin of Practical Psychology of Education, 2025)
Abstract Context and relevance. The subjectivity of the personality is the most important predictor of optimal self-development of a person. The theoretical basis of the study was the subject-activity approach, focusing on the sources and mechanisms of activating the process of personality development, including in the context of educational activities. Objective. To study theoretical and methodological approaches to the problem of professional self-determination as a condition for the development of individual subjectivity. Hypothesis. Professional self-determination, being a complex phenomenon, objectively determines a person's active position in relation to the world and himself in this world, including the formation of an individual personal-professional position, the design of one's own professional activity and optimal self-realization in it. Methods and materials. The study implemented a method of theoretical analysis of existing research in the field of interest to the authors. Results. Understanding subjectivity as an active-activity position of a person, considering self-determination as a need for self-development, and considering professional self-determination as the most important factor of self-determination and self-realization, we identified the key parameters of professional self-determination of an individual, which made it possible to develop a program aimed at studying the characteristics of professional self-determination of modern youth. Conclusions. The pilot testing of the developed diagnostic program objectively proved its informativeness and the possibility of wide application in the context of studying the characteristics of professional self-determination as a condition for the development of personal subjectivity. Резюме Контекст и актуальность. Субъектность личности выступает важнейшим предиктором оптимального саморазвития человека. Теоретическую основу исследования составил субъектно-деятельностный подход, акцентирующий внимание на источниках и механизмах активизации процесса развития личности, в том числе в условиях образовательной деятельности. Цель. Изучить теоретико-методологические подходы к проблеме профессионального самоопределения как условия развития субъектности личности. Гипотеза. Профессиональное самоопределение, являясь комплексным феноменом, объективно обусловливает активно-деятельностную позицию человека в отношении мира и себя в этом мире, включая формирование индивидуальной личностно-профессиональной позиции, проектирование собственной профессиональной деятельности и оптимальную самореализацию в ней. Методы и материалы. В исследовании был реализован метод теоретического анализа имеющихся исследований в области интересующей авторов проблематики. Результаты. Понимая под субъектностью активно-деятельностную позицию человека, самоопределение рассматривая как потребность в саморазвитии, а важнейшим фактором самоопределения и самореализации считая самоопределение профессиональное, мы выделили ключевые параметры профессионального самоопределения личности, позволившие разработать программу, направленную на изучение особенностей профессионального самоопределения современной молодежи. Выводы. Пилотажная апробация разработанной диагностической программы объективно доказала ее информативность и возможность широкого применения в рамках изучения особенностей профессионального самоопределения как условия развития субъектности личности.